2016
DOI: 10.1021/acs.jafc.6b00328
|View full text |Cite
|
Sign up to set email alerts
|

Phaseolus vulgaris L. Seedlings Exposed to Prometryn Herbicide Contaminated Soil Trigger an Oxidative Stress Response

Abstract: Herbicides from the family of S-triazines, such as prometryn, have been widely used in crop production and can constitute an environmental pollution in both water and soil. As a valuable crop, the common bean (Phaseolus vulgaris L.) is grown all over the world and could be exposed to such herbicides. We wanted to investigate the possible stress sustained by the common bean growing in prometryn-polluted soil. Two situations were observed: when soil was treated with ≥100 μM prometryn, some, but not all, measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 110 publications
2
17
0
Order By: Relevance
“…However, the declination in CAT activity at the highest dose (0.52 g/L) reflected that H 2 O 2 was not efficiently detoxified by this enzyme. The observed high MDA content in the present work indicated high H 2 O 2 level that was correlated to the inhibition of CAT activity 63 . Lowering in GST activity at 0.52 g/L concentration indicated the sensitivity of enzyme.…”
Section: Resultssupporting
confidence: 68%
“…However, the declination in CAT activity at the highest dose (0.52 g/L) reflected that H 2 O 2 was not efficiently detoxified by this enzyme. The observed high MDA content in the present work indicated high H 2 O 2 level that was correlated to the inhibition of CAT activity 63 . Lowering in GST activity at 0.52 g/L concentration indicated the sensitivity of enzyme.…”
Section: Resultssupporting
confidence: 68%
“…Boulahia et al 1 showed that exposing seeds to prometryn could trigger a significant oxidative stress response. When the soil was treated with prometryn at concentrations of 100 µM or more, the cells began to produce ROS, which had a harmful effect on seed growth.…”
Section: Discussionmentioning
confidence: 99%
“…19 These actions eventually result in the accumulation of ROS in body cells and induce oxidative stress. 1,20 Photosynthetic electron transport chains have many similarities to other electron transport chains. Therefore, we speculate that prometryn induces oxidative stress in human and animal cells in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the high KspsbA gene expression in kochia after atrazine application can be explained by the rapid turnover of the D1 protein. The photoinhibitory damage caused by atrazine also leads to production of reactive oxygen species (ROS) such as singlet oxygen ( 1 O 2 ) [35]. The singlet oxygen and the other free radicals produced after the blockage of electron transfer by triazines result in an irreversible damage to photosynthetic machinery contributing to plant death [36].…”
Section: Expression Of Target-site Genes Upon Herbicide Treatmentsmentioning
confidence: 99%